2021
DOI: 10.7759/cureus.13454
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Among Pregnant Women in Saudi Arabia: A Retrospective Single-Center Medical Record Review

Abstract: Background Obesity in Saudi Arabia is on the rise, especially among females who are more likely to suffer from obesity in the reproductive age group than males in the adult age group. Biologically, pregnancy can increase women’s weight and put them at greater risk for adverse obstetric outcomes. Objectives To find the prevalence of obesity among pregnant women and their obstetric outcomes. Methods This retrospective study was conducted on pregnant women wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The majority of the study participants were obese (42.4%) and overweight (28.8%). The same results were found in different Saudi epidemiological studies which reported increased obesity rates in pregnant and nonpregnant Saudi females [ 40 44 ].…”
Section: Discussionsupporting
confidence: 86%
“…The majority of the study participants were obese (42.4%) and overweight (28.8%). The same results were found in different Saudi epidemiological studies which reported increased obesity rates in pregnant and nonpregnant Saudi females [ 40 44 ].…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, the present study’s finding disagrees with a study conducted in Buriada, Saudi Arabia, where 30% of the sample was reported to be obese [ 20 ]. Likewise, a study carried out by Fallatah, Alnoury, and Fallatah et al, 2021, showed that 25% of the study sample were obese, which is consistent with the findings of a study conducted in Al-Hassa, Saudi Arabia, where the prevalence of obesity was 29% [ 21 , 22 ]. Comparing the prevalence rates of obesity at international and national levels can be challenging due to several factors, including the divergences in sampling methods, study designs, cultural behaviors, and lifestyle patterns across different countries.…”
Section: Discussionsupporting
confidence: 84%
“…This should be considered as a key factor in future data collection for research, particularly as female obesity has increased in Saudi Arabia over the last decade [ 119 ]. A further limitation of the current study is the use of controls from existing hospital records.…”
Section: Discussionmentioning
confidence: 99%